(untitled) (The South East European Journal of Economics and Business, 2019)
Following competing theories, the paper brings the determinants of the Serbian and Romanian current account dynamics with policy implications. The research sample consists of quarterly time series data over the period 2004q1–2017q2 and 2007q1-2017q4 for the Serbian and the Romanian case, respectively. Based on the state space model with time-varying parameters (TVP) approach, accurate and more robust estimates of responses to changes in the domestic demand real effective exchange rate and money supply were obtained. Consistently with theoretical foundations, the research findings suggest the country- specific policy mix for each country that might be effective to resolve the issue of the current account deficit.